EXPRESSION OF ORIENTAL IMAGERY IN THE UZBEK TRANSLATION OF HEINRICH HAYNE'S POEMS - Bozorova Mukhabat Abdurakhmonovna (Journals Park Publishing, 2023)
The article talks about the oriental image in the Uzbek translation of Heinrich Heine's poems, among which images occupy an important place. Heinrich Heine's poems were translated into Uzbek by the famous Uzbek poet Abdulla Sher. While reading these poems, it can be observed that the poet penetrated into the psyche of Hayne, and was able to skillfully convey the delicacy and artistic brilliance of the German language in the Uzbek language.
Keywords: image, motif, oriental style, lyrical hero.